Pengaruh Kompetensi Sosial Guru Pendidikan Agama Kristen Terhadap Motivasi Belajar Siswa Di Kelas XI SMK Negeri 1 Raya - Kurnia Novita Harianja; Tianggur Medi Napitupulu; Ronny Simatupang; Johari Manik; Sabar Rudi Sitompul (Universitas Maritim AMNI Semarang, 2024)
The aim of this research is to determine the positive and significant influence of the Social Competence of Christian Religious Education Teachers on Student Learning Motivation in class XI of SMK Negeri 1 Raya. The method used is a descriptive quantitative research method, with a population of 237 students and a sample taken of 25% so that the sample for this research is 59 students using Random Sampling techniques. The instrument used in this research used a closed questionnaire of 33 questions, of which 20 questionnaire items were for variable X and 20 items were for variable Y which had been tested on 33 students outside the research sample. The results of the research show that there is a positive and significant influence between the Social Competence of Christian Religious Education Teachers on Student Learning Motivation in class XI of SMK Negeri 1 Raya. 1) Test the relationship between rcount > rtable, namely 0.574>0.226; 2) Significant test tcount>ttable, namely 5.292>2.021; 3) Determination test, namely 32.94%; 4) The regression equation is obtained from Y ̂= 14.91+0.69X ; 5) Test the hypothesis using the F test to obtain Fcount > Ftable = (α= 0.05, dk numerator k = 19, dk denominator = n-2 = 59-2 = 57) namely 27.87> 1.40. Thus Ha, namely that there is a positive and significant influence between the Social Competence of Christian Religious Education Teachers on Student Learning Motivation in class XI of SMK Negeri 1 Raya is accepted and H0 is rejected.